Review Essay. Issue 3 (1st September 2018) - Edelheim, Johan R.
Innovation in Hospitality Education: Anticipating the Educational Needs of a Changing Profession, Jeroen A. Oskam, Daphne M. Dekker and Karoline Wiegerink (eds) (2018) Cham: Springer, 232 pp., ISBN: 9783319613789, h/bk, £99.99